2018
DOI: 10.1039/c8sc01142g
|View full text |Cite
|
Sign up to set email alerts
|

Oncosis-inducing cyclometalated iridium(iii) complexes

Abstract: A series of mitochondria-targeting cyclometalated iridium(iii) complexes activated the oncosis-specific protein porimin and calpain 1, and exhibited good inhibitory activities on a wide range of cancer types including drug-resistant cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 80 publications
5
89
0
1
Order By: Relevance
“…It was confirmed that ATP insufficient was one of the reason in oncosis. 11,17) At the same time, the result of DMF in our study had fully verified the common phenotype of oncosis. In the process of apoptosis, some chemotherapeutic agents cause ATP decrease, ROS accumulation, Ca 2+ elevation and MMP loss.…”
Section: Dmf Exert Potent Effect In Suppressing Proliferation Againstsupporting
confidence: 76%
See 2 more Smart Citations
“…It was confirmed that ATP insufficient was one of the reason in oncosis. 11,17) At the same time, the result of DMF in our study had fully verified the common phenotype of oncosis. In the process of apoptosis, some chemotherapeutic agents cause ATP decrease, ROS accumulation, Ca 2+ elevation and MMP loss.…”
Section: Dmf Exert Potent Effect In Suppressing Proliferation Againstsupporting
confidence: 76%
“…As documented that the ATP level plays an important role in cell death, which determine how the cell dies. 11,17) Mitochondrial dysfunction is one of the important features of programmed cell death (PCD). The loss of MMP and the opening of membrane permeability transition pore (PTP) related to cell death closely.…”
Section: Dmf Exert Potent Effect In Suppressing Proliferation Againstmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we further investigated whether complexes induce apoptosis through the mitochondrial damage by measuring the MMP changes . The MMP loss and the ROS overload are the main pathways in the mitochondria to carry out cell death , . We investigated the intracellular MMP loss and ROS production in Ru2 ‐treated A549 cells by using fluorescent probe JC‐1 and 2,7‐dichlorofluorescein diacetate (DCF‐DA) by flow cytometry respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Transition metal complexes remain a significant resource to produce chemical diversity in the search for new diagnostic and therapeutic agents, for a relatively readily subtle or dramatic change of the characteristics of the complex by alter‐related ligands. Therefore, biological applications of transition metal complexes have been greatly explored, especially in the anticancer drug development Cisplatin (CDDP), oxaliplatin (OXA), and carboplatin represent the most active and useful clinical transition metal anticancer agents, approximately nearly 50 % of all anticancer therapies globally. These drugs are especially effective in treating lung and ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%